2021
DOI: 10.3389/fpubh.2021.755252
|View full text |Cite
|
Sign up to set email alerts
|

Using Whole Genome Sequencing to Trace, Control and Characterize a Hospital Infection of IMP-4-Producing Klebsiella pneumoniae ST2253 in a Neonatal Unit in a Tertiary Hospital, China

Abstract: Background: The purpose of this study is to use whole genome sequencing (WGS) combined with epidemiological data to track a hospital infection of the carbapenem-resistant Klebsiella pneumoniae (CRKP), which affected 3 neonatal patients in the neonatal intensive care unit (NICU).Methods: The minimum inhibitory concentrations for the antimicrobial agents were determined according to the guidelines of the Clinical and Laboratory Standards Institute. Beta-lactamases were investigated using the polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…And there have also been sporadic epidemics caused by IMPKsp strains. IMP-38-producing ST307 K. pneumoniae strains and IMP-4-producing ST2253 K. pneumoniae infected neonatal patients in the neonatal ward in Shandong and Hunan province, respectively 11 , 32 . This again is consistent with our findings that there was a regional spread of ST307 IMPKsp strains carrying IMP-38 carbapenemases in Hunan province.…”
Section: Discussionmentioning
confidence: 99%
“…And there have also been sporadic epidemics caused by IMPKsp strains. IMP-38-producing ST307 K. pneumoniae strains and IMP-4-producing ST2253 K. pneumoniae infected neonatal patients in the neonatal ward in Shandong and Hunan province, respectively 11 , 32 . This again is consistent with our findings that there was a regional spread of ST307 IMPKsp strains carrying IMP-38 carbapenemases in Hunan province.…”
Section: Discussionmentioning
confidence: 99%
“…None of the infants exhibited infection with CP-CRE. 13 Seesahai et al have found that simple infection control measures involving contact precautions, staff education, and parental cohorting can be useful and cost-effective in preventing transmission. Attention to NICUspecific measures, including screening of at-risk mothers (in vitro fertilization conception) and their probands, careful handling of breastmilk, judicious antibiotic choice, and duration of treatment, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The production of IMP and VIM enzymes by Klebsiella pneumoniae isolates is rare in China. At present, IMP-4-producing Klebsiella pneumoniae has caused outbreaks in a few hospitals in China in recent years, 18 while IMP-8-producing Klebsiella pneumoniae has only been reported in Taiwan, 19 which has not been reported in pediatric patients. Only one case of IMP-26- 20 and IMP-38- 21 producing Klebsiella pneumoniae has been reported in China.…”
Section: Introductionmentioning
confidence: 99%